EFFECT OF PBV, QR, NPM, DER, CR, TATTOO ON STOCK PRICES IN PROPERTY & REAL ESTATE COMPANIES - Bayu Wulandari; Debby Sarah Sormin; Isti Ayuning Wigo; Eunike Mia Sundari Sianturi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to determine the effect of price book value, quicki ratio, net profit ratio, debt to equity ratio, current ratio, and total asset turnover on stock prices. This research was conducted on service companies in the real estate sub-industry from 2018 to 2020. The object of research is 65 (sixty five) companies listed on the Indonesia Stock Exchange. The sampling technique used in this study was purposive sampling, and a total sample of 45 (forty five) companies was obtained. The data used is the financial statements of each sample company published on the website www.idx.co.id. The research method used is quantitative analysis method because the data are in the form of numerical data and empirical data. While the selected variables are in the form of units that can be calculated and measured. The results showed that partially the price book value, quick ratio, net profit margin, debt to equity ratio, current ratio, and total asset turnover had no significant effect on stock prices